2021
DOI: 10.3390/su13084126
|View full text |Cite
|
Sign up to set email alerts
|

Political Instability Equals the Collapse of Tourism in Ukraine?

Abstract: The purpose of this study was to determine how political instability influences inbound tourist flows in Ukrainian cities, performance of tourism-related businesses, and tourism-based profits in general. This study allows us to present the impact of various events on the tourism economy in Ukraine; however, the available secondary data with the unobserved component model procedure detection give only a general overview of the situation. Thus, interviews were conducted with experts, including managers of accomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Our findings are consistent with [86], who found that, due to political instability, both the foreigner and local tourist's traffic declined and revenues derived from foreign tourists declined too. Furthermore, on the foundation of these results, the null hypothesis of no asymmetric association can be rejected.…”
Section: Non-linear Ardl Estimationssupporting
confidence: 92%
“…Our findings are consistent with [86], who found that, due to political instability, both the foreigner and local tourist's traffic declined and revenues derived from foreign tourists declined too. Furthermore, on the foundation of these results, the null hypothesis of no asymmetric association can be rejected.…”
Section: Non-linear Ardl Estimationssupporting
confidence: 92%
“…In the current context of the Russian–Ukraine war breaking up Ukraine. The Donbas and Crimea are the “lost land” from 2014, and sentimental tourism is the corollary (Tomczewska-Popowycz and Quirini-Popławski, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research was undertaken during the long-term political instability in Ukraine (since 2014), affecting tourism flows, especially people with a low sense of security (Tomczewska-Popowycz and Quirini-Popławski, 2021). Future research may look at other regions historically and/or culturally linked to the country of origin of tourists to investigate the motivations and behaviour of sentimental tourists at other destinations described in the Introduction.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Violent and non-violent political instability poses a significant risk to the tourism industry (Elit and Einav, 2004;Jong-A-Pin 2009;Naudé and Saayman, 2005). This holds in the case of developing countries (Dibeh et al, 2020;Ioannides and Apostolopoulos, 1999;Tomczewka-Popowycz and Quirini-Poplawski, 2021) and developed countries ( Álvarez-Díaz et al, 2019;Perles-Ribes et al, 2019). Furthermore, there is evidence from cross-country analysis regrouping emerging and advanced economies.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%